Introducing regional culture: analysis of curriculum management with local content of banyumasan culture at elementary school indonesia - Maspupah, Ulpah; Mayasari, Novi; Huda, Muhammad Nur (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
In facing the situation of globalization, which is increasingly developing rapidly, it can influence the mental, moral, and behavioral development of Indonesian society. It is necessary to introduce regional culture to realize the inheritance of cultural wealth, which has noble values that are very suitable for protecting oneself from the effects of globalization, which do not follow the personality of the Indonesian nation. Therefore, there is a need for curriculum development that is based on local wisdom. This research method is descriptive qualitative and case study. Data collection techniques include interviews, observation, and documentation. The data analysis used the Miles and Huberman model, which consists of data reduction, data presentation, and conclusions. The results of this research showed that curriculum management with local content of Banyumasan culture at SD Negeri 4 Grendeng includes planning, organizing implementation, and evaluation. The organization of the material consists of Manners in the School Environment, Manners Outside the School, the Process of Making Soy Tempe and Mendoan, Typical Banyumas Food Tempe Chips, Traditional Banyumas Game Dam-daman, Banyumas Traditional Art